Recent Progress on Metal‐Based Nanomaterials: Fabrications, Optical Properties, and Applications in Ultrafast Photonics (Adv. Funct. Mater. 49/2021). (2nd December 2021) - Fu, Bo; Sun, Jingxuan; Cheng, Yuan; Ouyang, Hao; Compagnini, Giuseppe; Yin, Peng; Wei, Songrui; Li, Shaojuan; Li, Dabing; Scardaci, Vittorio; Zhang, Han
Abstract : Metal‐Based Nanomaterials In article number 2107363, Vittorio Scardaci, Han Zhang, and co‐workers focus on metal‐based nanomaterials, including pure metal and metal oxide nanoparticles. The typical fabrication methods and excellent optical properties are illustrated in detail, which promote the potential applications enabled by metal‐based nanomaterials in ultrafast photonics.